Association of obesity on short- and long-term survival in patients with moderate to severe pneumonia-related ARDS: a retrospective cohort study - Arnaud Gacouin; Adel Maamar; Nicolas Terzi; Jean-Marc Tadié (BMC Pulmonary Medicine)
Abstract Background The incidence of obesity among patients admitted to the intensive care unit (ICU) is increasing, and pneumonia remains the leading cause of acute respiratory distress syndrome (ARDS). The association of obesity on both short- and long-term outcomes in patients with pneumonia-induced ARDS has been the subject of only limited research. Methods We conducted a retrospective analysis of a prospective cohort consisting of ARDS patients who had microbiologically confirmed pneumonia and a PaO2/FiO2 ratio ≤ 150 mmHg. Patients were assessed for mortality at 28 days, 90 days, and at 1 year from the diagnosis of ARDS and compared between obese defined by a body mass index (BMI) ≥ 30 kg.m2 and non-obese patients. Models were adjusted for age, sex, COPD, coronary artery disease, immunodepression, severity score and acute kidney injury on admission to the ICU, severity of ARDS (PaO2/FiO2 ratio ≤ 100 mmHg), severe hypercapnia (PaCO2 ≥ 50 mmHg), ventilatory ratio and plateau pressure the first day of ARDS, influenza, COVID-19, pneumocystosis, and bacteria involved in pneumonia. We also investigated the continuous spectrum of BMI on the risk of mortality. Results Of 603 patients, 227 patients (37.6%) were obese. Obesity was associated with female gender (p = 0.009), hypertension (p < 0.001), diabetes mellitus (p < 0.001), COVID-19 pneumonia (p = 0.008), and PaO2/FiO2 ratio ≤ 100 mmHg (p = 0.006). Obesity was independently associated with lower mortality at 28 days (adjusted Odds Ratio (OR) 0.55, 95% confident interval (CI) 0.33–0.90, p = 0.02) but not at 90 days (adjusted OR 0.70, 95% CI 0.45–1.09, p = 0.11) nor at 1 year from the diagnosis of ARDS (adjusted OR 0.73, 95% CI 0.47–1.13, p = 0.16). Mortality at 28 days was significantly lower in obese patients than in non-obese patients when propensity score matching was used (15.2% versus 22%, p = 0.04). BMI was also independently associated with lower mortality at 28 days (p = 0.038) but not with mortality at 90 days (p = 0.12) and 1 year (p = 0.12). Conclusion Our results suggest that in patients with pneumonia-related ARDS, obesity is independently associated with better survival at 28 days but not at 90 days and 1 year from the diagnosis of ARDS.